Maximizing Value: Linking Climate Change Action and Well-Being in CIties. - Ake, Kimberly. (2017)
Abstract: Cities are heavy emitters of GHG emissions and serve as centers of innovation for climate change action. However, with limited resources, they must establish priorities. As cities also become increasingly interested in improving quality of life and livability, connecting these themes to climate action has increasing salience. This thesis explores how cities might use climate action to improve resident well-being. The Gallup-Healthways Well-Being Index is examined as a long-term standard for cities to track trends in resident well-being against efforts to address climate change. Four cities in the Great Lakes Region are studied for their approach to managing environmental, health, and social consequences of climate change. Results suggest that cities in this region are making connections between actions that both address climate change and improve well-being, although sometimes not explicitly. In the context of climate adaptation, however, case cities overlooked infrastructure improvement and risk assessment in favor of visible short-term projects.; Thesis (M.A.)--Tufts University, 2012.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Ann Rappaport.; Committee: Julian Agyeman.; Keywords: Climate change, and Urban planning.